2011
DOI: 10.1002/jcc.21743
|View full text |Cite
|
Sign up to set email alerts
|

Franck–Condon simulation of the photoelectron spectrum of AsCl2 and the photodetachment spectrum of AsCl employing UCCSD(T)‐F12a potential energy functions: IE and EA of AsCl2

Abstract: The currently most reliable theoretical estimates of the adiabatic ionization energies (AIE(0)) from the X̃(2)B(1) state of AsCl(2) to the X̃(1)A(1) and ã(3)B(1) states of AsCl 2+, and the electron affinity (EA(0)) of AsCl(2) , including ΔZPE corrections, are calculated as 8.687(11), 11.320(23), and 1.845(12) eV, respectively (estimated uncertainties based on basis-set effects at the RCCSD(T) level). State-of-the-art ab initio calculations, which include RCCSD(T), CASSCF/MRCI, and explicitly correlated RHF/UCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 45 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…Employing the computed FCFs, we find that simulated photodetachment spectra obtained using these RCCSD(T) and UCCSD(T)-F12x PEFs are almost identical. This once again supports our previous conclusion [11][12][13] that the explicitly correlated method, UCCSD(T)-F12x, could be used to generate reliable PEFs in lieu of conventional correlated methods, such as RCCSD(T), at a considerably reduced cost. In addition, we have reported computed fundamental vibrational frequencies for P 2 H and P 2 H − for the first time, and these computed frequencies agree very well with available experimental values from the photodetachment spectrum of P 2 H − .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Employing the computed FCFs, we find that simulated photodetachment spectra obtained using these RCCSD(T) and UCCSD(T)-F12x PEFs are almost identical. This once again supports our previous conclusion [11][12][13] that the explicitly correlated method, UCCSD(T)-F12x, could be used to generate reliable PEFs in lieu of conventional correlated methods, such as RCCSD(T), at a considerably reduced cost. In addition, we have reported computed fundamental vibrational frequencies for P 2 H and P 2 H − for the first time, and these computed frequencies agree very well with available experimental values from the photodetachment spectrum of P 2 H − .…”
Section: Discussionsupporting
confidence: 87%
“…The use of the UCCSD(T)-F12x method follows our recently published works on AsX 2 (X = H, F, or Cl), and their ions, [11][12][13] where Franck-Condon spectral simulations including allowance for anharmonicity were carried out on theÃ(0,0,0)-X SVL emission spectrum of AsH 2 , 11 the photoelectron spectra of AsF 2 and AsCl 2 , and the photodetachment spectra of AsF 2 − and AsCl 2 − , 12, 13 using UCCSD(T)-F12x potential energy functions (PEFs). In these studies, [11][12][13] it was concluded that the explicitly correlated method, UCCSD(T)-F12x, could be used to generate reliable PEFs in lieu of conventional correlated methods, such as RCCSD(T), at a considerably reduced cost. Specifically, simulated spectra obtained using RCCSD(T)/aug-cc-pCV5Z and RHF/UCCSD(T)-F12a/aug-cc-pCVTZ PEFs are essentially identical (see Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have published high level ab initio calculations on AsX 2 , where X = H, F or Cl, and their ions. [1][2][3] In these studies, Franck-Condon spectral simulations were carried out on the A ˜(0,0,0)-X ˜SVL emission spectrum of AsH 2 , 1 the photoelectron spectra of AsF 2 and AsCl 2 , and the photodetachment spectra of AsF 2 À and AsCl 2 À . 2,3 In addition, the currently most reliable calculated values of the ionization energies and electron affinities of AsF 2 and AsCl 2 were reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In these studies, Franck-Condon spectral simulations were carried out on the A ˜(0,0,0)-X ˜SVL emission spectrum of AsH 2 , 1 the photoelectron spectra of AsF 2 and AsCl 2 , and the photodetachment spectra of AsF 2 À and AsCl 2 À . 2,3 In addition, the currently most reliable calculated values of the ionization energies and electron affinities of AsF 2 and AsCl 2 were reported. 2,3 In the course of these investigations, [1][2][3] it has come to our attention that, for some simple arsenic hydrides and halides, which are of particular importance in the microelectronics industry, 4 as well as in many other areas (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation